2020
DOI: 10.1542/peds.2019-3728
|View full text |Cite|
|
Sign up to set email alerts
|

Biomarkers and Disease Severity in Children With Community-Acquired Pneumonia

Abstract: BACKGROUND: Host biomarkers predict disease severity in adults with community-acquired pneumonia (CAP). We evaluated the association of the white blood cell (WBC) count, absolute neutrophil count (ANC), C-reactive protein (CRP), and procalcitonin with the development of severe outcomes in children with CAP. METHODS:We performed a prospective cohort study of children 3 months to 18 years of age with CAP in the emergency department. The primary outcome was disease severity: mild (discharged from the hospital), m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
2
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 32 publications
5
78
2
5
Order By: Relevance
“…The present study evaluated host biomarkers like theTLC count, which was useful only in the presence of moderate leukocytosis. Generally, like the conclusion in other studies, it can be concluded that TLC and neutrophil percentage were not useful in distinguishing pneumonia from severe disease [40]. However, a CRP cut-off of 20 mg/L had a high specificity (90%) and positive predictive value (92%) to distinguish non-severe from severe disease.…”
Section: Discussionsupporting
confidence: 64%
“…The present study evaluated host biomarkers like theTLC count, which was useful only in the presence of moderate leukocytosis. Generally, like the conclusion in other studies, it can be concluded that TLC and neutrophil percentage were not useful in distinguishing pneumonia from severe disease [40]. However, a CRP cut-off of 20 mg/L had a high specificity (90%) and positive predictive value (92%) to distinguish non-severe from severe disease.…”
Section: Discussionsupporting
confidence: 64%
“…The diagnostic utility of inflammatory markers in pediatric community‐acquired pneumonia (CAP) has been reported in the post‐pneumococcal vaccination era 4 . Several biomarkers are used for treatment evaluation in pediatric patients with pneumonia 5,6 . C‐reactive protein (CRP) is a serum biomarker useful for the treatment evaluation of pneumonia due to its high correlation with etiology and severity 4,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, a 2008 meta‐analysis including a total of 1230 children concluded that an elevated concentration of CRP only weakly predicts a bacterial aetiology 8 . Yet other studies suggest that CRP can be a useful prognostic marker for pneumonia‐associated complications, 9‐14 and especially severe complications such as the need for a chest drain 15 …”
Section: Introductionmentioning
confidence: 99%